Astragaloside IV Derivative (LS-102) Alleviated Myocardial Ischemia Reperfusion Injury by Inhibiting Drp1Ser616 Phosphorylation-Mediated Mitochondrial Fission - Li Chen; Li Chen; Xiao-Yi Chen; Qian-Long Wang; Si-Jin Yang; Hua Zhou; Li-Sheng Ding; Lin-Sen Qing; Pei Luo (Frontiers Media S.A., 2020)
Our previous studies showed that Astragaloside IV derivative (LS-102) exhibited potent protective function against ischemia reperfusion (I/R) injury, but little is known about the mechanisms. Mitochondrial fission regulated by dynamin-related protein1 (Drp1) is a newly recognized determinant of mitochondrial function. This study aimed to investigate the protection of LS-102 on mitochondrial structure and function by regulating the activity of Drp1 using models of H9c2 cardiomyocyte injury induced by hypoxia-reperfusion (H/R), and rat heart injury induced by I/R. The results showed that LS-102 significantly decreased apoptosis, levels of ROS, CK, LDH, and calcium, upregulating MMP, and the Bax/Bcl-2 ratio in cardiomyocytes during I/R injury. Furthermore, LS-102 prevented I/R-induced mitochondrial fission by decreasing Drp1's mitochondrial localization through decreasing the phosphorylation of Drp1 at Ser616 (Drp1Ser616) and increasing the phosphorylation of Drp1 at Ser637 (Drp1Ser637) in H9c2 cells. Importantly, we also robustly confirmed Drp1Ser616 as a novel GSK-3β phosphorylation site. GSK-3β-mediated phosphorylation at Drp1Ser616 may be associated with mitochondrial fission during I/R of cardiomyocytes. In conclusion, LS-102 exerts cardio protection against I/R-induced injury by inhibiting mitochondrial fission via blocking GSK-3β-mediated phosphorylation at Ser616 of Drp1.